Thermal death evaluation of multi-strains probiotic inoculant for shelf-life prediction - Thanyarat Naksing; Pratchaya Hatawee; Apinan Wanlapa; Kittikoon Torpol; Chiu, Chiu-Hsia; Jantima Teeka; Atsadawut Areesirisuk (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aimed to determine the thermal death kinetic of Lactobacillus plantarum 7-40, Bacillus subtilis E20, and Saccharomyces cerevisiae P13 contained in probiotic product and to study the relation of specific death rate (kd) and temperature following the Arrhenius equation for shelf-life prediction. The result showed that the viability of probiotic strains was differently affected by storage temperature. The B. subtilis E20 could survival more than L. plantarum 7-40 and S. cerevisiae P13 under high storage temperature. It was also found that the lowest kd was provided by B. subtilis. This result demonstrated that the B. subtilis was more stable than L. plantarum and S. cerevisiae during keeping under high-temperature warehouse. Thereby, the storage temperature of the multi-strains probiotics inoculant should be considered carefully. Also, the natural logarithm of kd was well related to the storage temperature as the Arrhenius equation. The Arrhenius model could be applied for predicting the shelf-life of probiotic inoculant as well. This study could be used for managing the stock of a multi-strains probiotic product in the high-temperature warehouse.